Evaluation of Pharmaceutical Wholesaler Supplier Performance in the Procurement Process at Puskesmas ABC Garut Regency - Ardi Rustamsyah, Ardi Rustamsyah; Aliep Topa Ubaddillah, Aliep Topa Ubaddillah; Raden Aldizal Mahendra Rizkio Syamsudin, Raden Aldizal Mahendra Rizkio Syamsudin (Jurnal Medika Farmaka, 2024)
The drug procurement process in the Health Center is highly dependent on the effectiveness of the supply chain run by Pharmaceutical Wholesalers (PBF). Supplier performance evaluation is important to ensure timely delivery, stock availability, and compliance with regulations. This study aims to analyze the performance of PBF suppliers in the drug procurement process at ABC Health Center, Garut Regency, and to identify factors that influence the efficiency and effectiveness of the pharmaceutical supply chain. This study uses a non-experimental descriptive method with the Supply Chain Operation Reference (SCOR) approach. The sampling technique uses purposive sampling with a population of pharmacists who are responsible for drug procurement at the Health Center and samples in the form of several PBFs. Data were collected through documentation (order letters and invoices) and interviews with related parties. The evaluation results showed variations in performance scores between PBFs, where only three PBFs obtained very good performance scores. However, the aspects of Responsiveness (timeliness of providing orders) and Agility (ability to adapt to changes in demand) are still major challenges. The factors that most influence supply chain efficiency are timely delivery, stock availability, coordination between PBF and the Health Center, and compliance with pharmaceutical regulations.